COMMODITIES AND HISTORY: A LITERATURE REVIEW ON COMMODITY HISTORIES - Dissanayake, Dilhani (PEOPLE: International Journal of Social Sciences, 2020)
Imperial commodities have been the subject of both popular and scholarly histories in recent years. A considerable amount of literature has been published on commodities such as tea, coffee, sugar, chocolate, tobacco, and spices such as pepper and cloves. Those commodity histories reveal the lure of exotics for Europeans, importantly the Portuguese, Dutch, Spanish and British, who engaged at various times in commercial imperialism, colonialism, capitalism, slave labour, commodity democratisation, changing diets and changing food habits. This paper presents a literature review on selected popular histories that examined commodities, for instance, Sidney W. Mintz’s Sweetness and Power (1986), Roy Moxham’s Tea: Addiction, Exploitation, and Empire (2004) and James Walvin’s Fruits of Empire: Exotic Produce and British Taste, 1660-1800 (1997). This literature review will help us to understand commodity histories literature in a broader perspective.